ANALISA IKLIM KOMUNIKASI DAN GAIRAH KERJA KARYAWAN DI BANK CAPITAL CABANG ASEMKA - Nurdin, Fany Wijaya (Jurnal Insani, 2015)
This study examines the climate issue of communication and morale of employeesin Capital Bank Asemka branch, Jakarta. This research aims to identify and analyze the communication climate and employees morale that is built in Capital Bank Asemka branch.This research uses qualitative descriptive method. This method is used to find and gather data, compile, use and interpret existing data. The data that is used in this study areobtained by written documents, consisting of books, archive, also gathered from an in-depth interview with the right sources of informant. The in-depth interviews were conducted by a list of questions that have been prepared. Before hand observation was also conducted to determine the situation on the ground. In this case, the researcher conducted participant observation with direct involvement role in a day-to-day activities with the informant.In this study the authors test the validity of data obtained using triangulation techniques. Triangulation is done by comparing or double checking the data that has been obtained, which is the results of both observations and interviews and other related documents.After analyzing, theauthor concluded that the communication climate that is built in Capital Bank Asemka branch is not conducive and has became one of the causes of low morale of every employee. One of the causes is because of the low factors that support the establishment of communication climate, such as trust, mutual decision-making, integrity, open communication downward, listen upward communication and emphasis to high performance goal. Hence, a low morale of work in employee is caused by factors that are not met. Whereas, a conducive communication climate can be realized with the role of a leader who can provide a good example for his subordinates, so that subordinates will gain a correct view in the organization and would encourage the morale of subordinates to work excellently for the company.